Success in national level junior tennis: Tactical perspectives - Klaus, A.; Bradshaw, R.; Young, W.; O'Brien, B.; Zois, J. (International Journal of Sports Science & Coaching, 2017)
Purpose: Point duration in competitive tennis is becoming shorter, highlighting a greater emphasis on performance of the first strokes of each point, in particular, the performance of the server. Methods: Descriptive measures of the video-based analysis included stroke type, point outcome and stroke position of the first two strokes of the server (service and first shot) during 10 randomly selected sets of competition on hard court. All participants (male; n=8) were of the age group 14 years and below and competed in national level events. Results: The performance of the first serve is characterized by an "in-percentage" of 54.6% and an improved chance of winning the point (for the server) following a first serve (55.9%; P<0.001) compared to a second serve (42.9%). The majority of stroke positions for first-shot winners were located in the central zone of the court (52.1%; P<0.01). In comparison to the error rate of all examined strokes, we observed an increased error rate of the first shot (16.5% vs. 22.4%; P<0.01). Conclusion: Contrasting to professionals, juniors produce more first-serve errors and win fewer points directly via the serve. Success in junior tennis relies in minimizing errors within short rallies specifically on the first shot of the server. Coaches of national level junior tennis players should focus on strategies to optimize court position following the serve and service percentage to increase competitive success rate. To achieve this, the server should utilize the serve as a "set-up" tool, dictating the direction of the returner's return of serve within the central zones of the court. ABSTRACT FROM AUTHOR